Hydroxyapatite coating containing multi-walled carbon nanotubes on AZ31 magnesium: Mechanical-electrochemical degradation in a physiological environment. Issue 7 (May 2018) - Mohajernia, Shiva; Pour-Ali, Sadegh; Hejazi, Seyedsina; Saremi, Mohsen; Kiani-Rashid, Ali-Reza
Abstract: To control the degradation of magnesium alloys and improve the mechanical performance of common hydroxyapatite (HAp) coatings, a HAp coating containing multi-walled carbon nanotubes (MWCNT) was applied on AZ31 magnesium alloy using plasma spray technique. The coating properties including thickness and morphology, phase analysis and toughness were characterized through SEM, XRD, and indentation methods, respectively. Biodegradation behavior in the presence and absence of slow strain rate test (SSRT) was then thoroughly examined in a simulated body fluid (SBF). The results demonstrated that the stress corrosion cracking (SCC) susceptibility of AZ31 Mg alloy is decreased from 26.8% (HAp coated sample) to 9.8% (HAp/MWCNTs coated one). The combination of microscopic observations as well as mechanical-electrochemical degradation data for long exposure times, suggests that the bridging effect of MWCNTs among molten HAp splats plays a key role in the improvement of mechanical properties and consequently both electrochemical and stress corrosion performances of HAp coating.